2018
DOI: 10.2741/e823
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid nullified aluminium toxicity in in vitro model of Alzheimer rsquo s disease

Abstract: Aluminium (Al) is a ubiquitously distributed environmental toxicant that lacks biological functions; however, its accumulation in the brain has been demonstrated to be linked to several neuropathological conditions particularly Alzheimer's disease (AD). Asiatic acid (AA), a triterpene extracted from , has been reported to cross the blood brain barrier and also displayed antioxidant and neuroprotective activities. The present study was aimed to explore the neuroprotective effect of AA against aluminium maltolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…More importantly, C. asiatica and its extracts improved neurological diseases by reducing inflammatory factors, balancing oxidative stress, repairing abnormal expression of mitochondrial-related proteins, and improving the content of BDNF. In addition, they reduced related nerve cell apoptosis, increased synaptic density, and improved the survival rate of neural cells (Chaisawang et al, 2017;Gray et al, 2018a;Rather et al, 2018b).…”
Section: Effects On Neurological Diseasesmentioning
confidence: 98%
“…More importantly, C. asiatica and its extracts improved neurological diseases by reducing inflammatory factors, balancing oxidative stress, repairing abnormal expression of mitochondrial-related proteins, and improving the content of BDNF. In addition, they reduced related nerve cell apoptosis, increased synaptic density, and improved the survival rate of neural cells (Chaisawang et al, 2017;Gray et al, 2018a;Rather et al, 2018b).…”
Section: Effects On Neurological Diseasesmentioning
confidence: 98%
“…Aluminum is a widely distributed environmental toxicant that upon accumulation in the brain shows associated with neurodegenerative diseases, especially AD. Recently, AA has showed neuroprotective against aluminum maltolate-induced neurotoxicity (Ahmad Rather et al, 2018 ). AA found to enhance cell viability, ameliorate mitochondrial membrane dysfunction, and resultant oxidative stress and apoptosis-regulating AKT/GSK-3β signaling pathway in neuroblastoma cells (SH-SY5Y).…”
Section: Asiatic Acid In Alzheimer's Diseasementioning
confidence: 99%
“…AA mitigated rise in aluminum, activity of acetylcholinesterase and gamma secretases along with amyloid β 1−42 , glial fibrillary acidic protein and ionized calcium binding adaptor molecule-1. AA also reduced inflammatory mediators iNOS, COX-2, and NF-κB in the hippocampus and cortex (Ahmad Rather et al, 2018 ).…”
Section: Asiatic Acid In Alzheimer's Diseasementioning
confidence: 99%
“…AA derivatives have been shown to counteract glutamate-induced excitotoxicity in nerve cells (Lee et al ., 2000), while asiaticoside derivatives can antagonize β-amyloid-induced nerve damage (Jew et al ., 2010; Mook-Jung et al ., 2015). Furthermore, AA shows neuroprotective effects against aluminum-induced neuronal toxicity in vivo and in vitro (Ahmad et al ., 2018a, 2018b). Xiong has shown that rotenone or H 2 O 2 can reduce the mitochondrial membrane potential (MMP) of SH-SY5Y DA cells.…”
Section: Introductionmentioning
confidence: 99%